The Improvement of Discharge Capacity of Zr-doped Lithium Titanate for Lithium Ion Batteries - Chen Yongjian; Mu Daobin; Hang Rong; Wu Borong (MATEC Web of Conferences, 2016)
Li4Ti5−xZrxO12 (0 ≪ x ≪ 0.05) materials are synthesized via one-step liquid method in this work. The morphology, elemental distribution and lithium storage performance of Zr-doped lithium titanate are systematic analyzed by field emitting scanning electron microscopy (FE-SEM, Hitachi S-4800), energy dispersive X-ray (EDS) and Land battery test system (LAND CT2001A) together with the pristine lithium titanate for comparison. The FE-SEM images show the uniform morphology and narrow particle size distribution of Zr-doped samples. The cycle performance measurements demonstrate that the Li4Ti4.97Zr0.03O12 electrode displays the best discharge capacities among the composites. It delivers the initial discharge capacities of 165.4 mAh/g and 152.9 mAh/g at 5C and 10C, and remains the values of 142.9 mAh/g and 127.4 mAh/g after 200 cycles. Furthermore, the charge and discharge curves exhibit that the Zr-doped composite presents smaller polarization than the pristine lithium titanate.